Carbon thin film deposition on plastic using FCVA - Ng, BIlly Chee Wan (2017)
Carbon thin film technology has been present in many present applications, the type of substrate it can be deposited on, varies from metal to non-metal. Filtered Cathodic Vacuum Arc (FCVA) is one commonly used technique to deposit carbon thin film. This project will be using FCVA as the main deposition technique, parameters such as temperature and substrate bias affecting the surface energy are varied. Temperature is varied from 10 to 600 degree Celsius, while the substrate bias is varied from 0V to 600V. Results shows that initial deposition on carbon surface can reach a very low surface energy and achieve a contact angle of 1060. The optimal condition to achieve this low surface energy is 300V substrate bias and 500 degree Celsius. As the objective of the project is to achieve super-hydrophobic surface or contact angle more than 1600, surface modification is suggested and done using post treatment techniques. The highest contact angle sample from the initial deposition is adopted to further reduce the surface energy. Post treatment using plasma technique is used, contact angle measurement was recorded once again to compare the effectiveness of the plasma technique. CF4 and SF6 plasma is used for this post treatment. Negative results has been recorded and these gases has proven to improve the hydrophilicity of the surface instead of improving the hydrophobicity of the surface.